2019
DOI: 10.1186/s12916-019-1354-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on pregnancy outcomes in a freeze-all policy: an analysis of 22,043 first autologous frozen-thawed embryo transfer cycles in China

Abstract: Background Abnormal BMI is associated with discouraging IVF outcomes in fresh autologous or oocyte donor cycles, whether or not such a relation also holds true for women undergoing frozen-thawed embryo transfer (FET) remains unknown. In addition, it remains unclear the detrimental effect of abnormal BMI on IVF outcomes occurs at the level of ovary or endometrium. Methods A retrospective study involved 22,043 first FET cycles of all women who had undergone a freeze-all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 35 publications
4
63
1
2
Order By: Relevance
“…They found no statistically significant differences in the implantation rate or live-birth rate among underweight (<18.5 kg/m 2 ), normal weight (18.5-24.9 kg/m 2 ), overweight (25.0-29.9 kg/m 2 ), and obese (≥30.0 kg/m 2 ) women. In contrast, a retrospective study found that obesity was associated with declines in the clinical pregnancy rate and LBR (18). In our study, the number of patients with a BMI ≥ 30 kg/m 2 was only 14, which was a small number of patients.…”
Section: Discussioncontrasting
confidence: 74%
“…They found no statistically significant differences in the implantation rate or live-birth rate among underweight (<18.5 kg/m 2 ), normal weight (18.5-24.9 kg/m 2 ), overweight (25.0-29.9 kg/m 2 ), and obese (≥30.0 kg/m 2 ) women. In contrast, a retrospective study found that obesity was associated with declines in the clinical pregnancy rate and LBR (18). In our study, the number of patients with a BMI ≥ 30 kg/m 2 was only 14, which was a small number of patients.…”
Section: Discussioncontrasting
confidence: 74%
“…The effects of female age, [24–26] D3 embryo transfer, [27] and BMI [28,29] on pregnancy outcomes in patients undergoing in vitro fertilization have been demonstrated in many previous studies. Therefore, it is no longer necessary to explain the influence of the above factors on LBR.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial preparation of HRT was performed as described previously. 27 , 28 In short, oral E2 (ethinyloestradiol 75 µg daily, Shanghai Xinyi Pharma, China; or fematon 4 mg, twice daily, Abbott Healthcare Products B.V.) was commenced on the third day of the menstrual cycle; progesterone exposure was initiated when the endometrial thickness reached ≥7 mm. Embryo transfer was performed 3 days after progesterone administration for day 3 embryos or 5 days later for blastocysts.…”
Section: Methodsmentioning
confidence: 99%